Time- and concentration-dependent expression of immune and barrier genes in the RTgutGC fish intestinal model following immune stimulation. Issue 88 (May 2019) - Schug, Hannah; Yue, Yang; Krese, Rok; Fischer, Stephan; Kortner, Trond M.; Schirmer, Kristin
Abstract: The fish intestine comprises an important environment-organism interface that is vital to fish growth, health and pathogen defense. Yet, knowledge about the physiology and defense mechanisms toward environmental stressors, such as bacterial or viral cues, is limited and depends largely on in vivo experiments with fish. On this background, we here explore the immune competence of a recently established in vitro intestinal barrier model based on the rainbow trout ( Oncorhynchus mykiss ) intestinal epithelial cell line, RTgutGC. We demonstrate that the RTgutGC cell barrier reacts to two immune stimuli, the bacterial lipopolysaccharide (LPS) from Escherichia coli and the viral Poly(I:C), by regulating the mRNA abundance of selected genes in a partly time- and concentration dependent manner. The immune stimuli activated the Myd88-and Ticam-dependent signalling cascades, which resulted in downstream activation of pro-inflammatory cytokines and interferon, comparable to the regulatory patterns known from in vivo . Stimuli exposure furthermore influenced the regulation of epithelial barrier markers and resulted in slightly impaired barrier functionality after long-term exposure to LPS. Collectively, we provide proof of the usefulness of this unique cell culture model to further gain basic understanding of the fish innate immune system and to apply it in various fields, such as fish feed development and fish health in aquaculture or the evaluation of immuno-toxicity of chemical contaminants.